Lin Litchfield interviewed by Hazel de Berg in the Hazel de Berg collection - Litchfield, Lin.; De Berg, Hazel, 1913-1984. (1966)
Litchfield speaks of her early life in country New South Wales; memories of the landscape; her early art studies; the techniques she uses; influences in her work and the subjects that interest her.
Digital master available
Transcript available (3 p.)
Keywords: Litchfield, Lin -- Interviews; Women painters -- Australia -- Interviews